Adolescents` willpower building methods in sports - Bozhkova, G. N.; Bykov, A. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes an athletic physical fitness improvement concept facilitated by the relevant fiction literature to help form a mentally balanced and broadly developed personality and, hence, contribute to the competitive successes. Objective of the study was to analyze the adolescents` willpower building methods with the role models provided by the heroic characters in the Russian and foreign fiction for the last centuries. For the purposes of the study we selected the "Silver Skates" novel by M.M. Dodge, the writer from Holland, and "Flute for the Champion" novel by V.V. Medvedev to find and explore benefits of the binary and quasi-motor methods for the athlete`s mental development process. The study shows that the best sports-featuring novels may be applied as efficient tools for the sporting adolescents` willpower building purposes.